Students’ Self-Efficacy Profiles in Solving Algebraic Form Problems in Class Vii An-Najah Smp It Al-Fahmi Palu Based on Mathematical Ability - Salza Billa Aulia Barani; Gandug Sugita; Anggraini Anggraini; Mustamin Idris (FKIP - Universitas Riau, 2026)
Difficulties among students in solving algebraic word problems are still frequently found in junior high school mathematics learning. These difficulties are not only caused by weak conceptual understanding but also by students’ low confidence in their own abilities. Self-efficacy plays an important role in determining students’ persistence, strategies, and success in solving mathematical problems. This study aims to describe students’ self-efficacy profiles in solving algebraic word problems based on mathematical ability. This research employed a qualitative descriptive approach. The research subjects were three students of class VII SMP IT Al-Fahmi Palu with high, medium, and low mathematical ability, determined based on their mathematics report card scores. Data were collected through written tests consisting of algebraic word problems and semi-structured interviews. Data analysis was conducted through data condensation, data display, and conclusion drawing. The findings show that students with high mathematical ability fulfill all self-efficacy indicators across the dimensions of level, strength, and generality. Students with medium mathematical ability fulfill some indicators but still show hesitation at several stages, while students with low mathematical ability are not yet able to optimally fulfill self-efficacy indicators. This study concludes that students’ self-efficacy profiles differ according to their level of mathematical ability.